Human existence in Kafka’s The Metamorphosis - Marwan Kadhim Mohammed (Social Sciences and Humanities Open)
Franz Kafka's novella The Metamorphosis poses a formidable challenge to many philosophical ideas concerning human existence. The novella has been widely studied through psychoanalytic, social, existential, and theological lenses. However, there remains a need to highlight how Nietzsche's philosophical conceptions of existence can offer a deeper, and perhaps underexplored, understanding of its protagonist's transformation. This study aims to investigate The Metamorphosis to question human existence through the interdependence between Kafka's novella and Nietzsche's philosophy of existence. The Nietzschean concepts of rejecting conventional values, individual will to power, and nihilism are adopted to examine Kafka’s protagonist’s transformation and experience as an insect. The study finds out that Kafka's novella The Metamorphosis presents a bleak, existential worldview, urging readers to reflect on the complexities of human existence. Adopting Nietzsche's philosophical perspective on existence as a method of analysis offers a new perspective for understanding these philosophical complexities. The study concludes that the interconnection between Kafka's novel and Nietzsche's concepts of human existence gives a new dimension to the protagonist’s character. Gregor's identity and status are challenged, and his human existence is threatened when he is transformed into a strange creature who has no right to exist.